2009
DOI: 10.1002/app.29980
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical modification of LDPE in single‐screw extruder

Abstract: The effect of processing history in a singlescrew extruder on molecular characteristics was studied by employing commercially available low-density polyethylene with no additives. Generation of long-chain branch, which is responsible for the neck-in phenomenon and draw resonance, is indicated by nonlinear viscoelastic properties of the extruded samples. Consequently, the processed samples show higher level of elastic property than the original pellet. However, thermal analysis revealed that there is no change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Moreover, some LDPE samples are known to be thermocomplex materials,45, 46, 49 although Stadler et al54 reported that LDPE used in their research obeys the time‐temperature superposition principle. This is reasonable because relaxation mechanism associated with long‐chain branches has different activation energy from that of entanglement couplings for a linear polyethylene 5, 52, 53. We confirmed that the present LDPE is also a thermocomplex material as demonstrated by a well‐known van Gurp–Palmen plot in our previous work 49…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, some LDPE samples are known to be thermocomplex materials,45, 46, 49 although Stadler et al54 reported that LDPE used in their research obeys the time‐temperature superposition principle. This is reasonable because relaxation mechanism associated with long‐chain branches has different activation energy from that of entanglement couplings for a linear polyethylene 5, 52, 53. We confirmed that the present LDPE is also a thermocomplex material as demonstrated by a well‐known van Gurp–Palmen plot in our previous work 49…”
Section: Resultssupporting
confidence: 90%
“…The flow activation energy is calculated to discuss the branch structure assuming that the time‐temperature superposition principle is applicable to the virgin LDPE and found to be ∼ 53 kJ/mol. The value, however, has no/little relation with, at least, long‐chain branch structure for a commercial LDPE,16 although it is known that longer branches provide higher activation energy employing model star‐branch polyethylenes 52, 53. This could be attributed to the complicated branch structure for a commercial LDPE.…”
Section: Resultsmentioning
confidence: 99%
“…The question arises as to whether amylose could undergo shear scission purely because its branches are long, as distinct from being a much smaller molecule than amylopectin (which as explained is susceptible to shear scission because it is so large and relatively inflexible, being comprised only of short highly connected branches). However, the branches in amylose, although long (say, DP ∼ 500), are much shorter than those in synthetic polymers which susceptible to shear scission . Thus, the individual branches of amylose will not be strongly prone to shear scission, although as noted above there can be some preferential scission of longer chains.…”
Section: Resultsmentioning
confidence: 99%
“…Some work has been conducted on degradation of polyethylene and polypropylene during extrusion where scission of long chain branches in polyethylene and chain scission of polypropylene has been reported, but as stated in these papers more detailed knowledge of macromolecular branching structure and degradation chemistry needs to be understood in explaining the degradation processes. The present study provides useful insight into these processes.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was found that the rheological properties and processability of the polymer composite containing PTFE fibers are dependent on the processing history to a great extent [15], which is similar to shear modification behavior of long-chain branched polymers [39][40][41][42]. The change of shape and dispersion state of PTFE fibers during processing would affect the rheological properties.…”
Section: Introductionmentioning
confidence: 99%